Elaborando o mapa turístico de Ourinhos através da percepção discente da escola EE Profª Josepha Cubas da Silva - Santos, Fernando Ribeiro dos [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Ourinhos municipality carries in its bygone days of great historical baggage, since its foundation near the Paranapanema River. Through museums, monuments and nature of the region, it is possible to observe how this municipality has developed over the years. In the modern world, the municipalities tend to develop local tourism, which turn out to be a contribution to its economy, generating employment and income for the receiving center. This current research associates the perception of elementary school students on the tourist potential of Ourinhos town, linked to the teaching of Geography, where tourism is part of the thematic axis of the discipline. From qualitative and quantitative interviews, through simple statistical models, it will be possible to observe the elementary schools students vision on this potential, and what measures should the city hall take connected to this treatment. At the end of the survey, it will be reported, the negative and positive points on which the government should pay attention to, in order to advance local tourism. At the end of the work, it will be elaborated a proposal of Ourinhos tourist map on which the municipality does not have, interpreting the perception of this population

O município de Ourinhos carrega consigo um pretérito de grande bagagem histórica, desde a sua fundação nas proximidades do rio Paranapanema. Através de museus, monumentos e natureza da região, é possível observar como esse município se desenvolveu com o passar dos anos. No mundo contemporâneo os municípios tendem a desenvolver o turismo local, onde o mesmo acaba contribuindo com a sua economia gerando emprego e renda para o núcleo receptor. A presente pesquisa associa a percepção dos estudantes do ensino fundamental em relação ao potencial turístico da cidade de Ourinhos, atrelado ao ensino de Geografia, onde o turismo faz parte do eixo temático da disciplina. A partir da realização de entrevistas qualitativas e quantitativas por meio de modelos estatísticos simples será possível observar qual a visão que os discentes têm deste potencial, e quais medidas a prefeitura municipal deverá tomar em relação a essa tratativa. Serão relatados no final da pesquisa os pontos negativos e positivos nos quais o governo devera atentar-se a fim de progredir o turismo local. No final do trabalho será elaborada uma proposta de mapa turístico de Ourinhos do qual o município não dispõe, interpretando a percepção desta população
Keywords: Turismo - Mapas; Percepção; Ourinhos (SP)